Literature Review: Psychological Resilience Factors in People with Neurodegenerative Diseases. (26th November 2019) - Ovaska-Stafford, Noora; Maltby, John; Dale, Maria
Abstract: Background: Psychological distress is frequently observed in neurodegenerative diseases (NDDs) having a significant impact on function, quality of life (QOL), caregiver burden, and illness cost. As higher psychological resilience can protect against negative outcomes and aid in the successful adjustment to illness, identifying resilience factors is important. Understanding what enhances or lowers psychological resilience allows us to offer support/interventions to people with NDDs and their carers starting early in the disease process. Objective: To investigate factors associated with psychological resilience in NDDs by completing a systematic review of relevant studies. Method: Five electronic databases were searched for studies relating to psychological resilience in NDDs. Eighteen articles were reviewed using a narrative synthesis approach. Results: Studies with varied aims and methodologies were found. The identified factors were categorized into core, internal, and external resilience. Regarding core factors contradicting evidence was found about the relationship between resilience and physical function. Fatigue, however, appears to be associated with less resilience. A limited number of studies focused on pain and demographics. Of internal resilience factors, studies found positive associations between higher resilience and improved mental health, even over time. Resilience appears to correlate positively with various psychological and QOL factors. Importantly, external resilience factors (e.g., social connectedness and intervention) were discovered to be linked to resilience. The evidence for resilience-enhancing intervention suggests that resilience can be modified. Conclusion: Various factors were identified to be associated with psychological resilience in NDDs. As resilience appears to be modifiable, it is important to focus on resilience-enhancing interventions for people with NDDs.